Алгоритм Очевидности Глушкова - Летичевский, А.А.; Лялецкий, А.В.; Мороховец, М.К. (Кибернетика и системный анализ, 2013)
Розглядаються загальні підходи В.М. Глушкова до проблеми штучного інтелекту. Зокрема, детально висвітлюється історія досліджень за програмою «Алгоритм Очевидності», ініційованою В.М. Глушковим. Аналізуються результати, одержані за цією програмою. V.M.Glushkov’s general approaches to the problem of artificial intelligence are considered. In particular, the history of investigations according to Evidence Algorithm program initiated by V.M.Glushkov is described in detail. Results obtained within this program are analysed.